Histologic evaluation of a Q-switched Nd:YAG laser in the nonablative treatment of wrinkles - David J. Goldberg (2018)
BACKGROUND. A variety of nonablative dermal remodeling techniques are currently available. The Q-switched Nd:YAG laser, in addition to its role in tattoo removal, hair removal, and vascular and pigmented lesion treatment, may also play a role in dermal remodeling for the treatment of wrinkles. The histologic changes seen in human skin after Q-switched Nd:YAG laser exposure have yet to be evaluated. OBJECTIVE. To study histologic changes after the use of a Q-switched Nd:YAG laser in the nonablative treatment of photoaged skin. METHODS. Sun-damaged infrauricular skin from six female subjects was exposed to a Q-switched Nd:YAG laser at fluences of 7 J/cm2with two laser passes. Histologic examinations were performed before laser treatment and 3 months later. RESULTS. Biopsy specimens showed slight fibrosis in the superficial papillary dermis with unremarkable epidermal changes. CONCLUSION. The Q-switched Nd:YAG laser produced morphologic changes similar to, but lesser in degree, than those seen with both CO2and Er:YAG laser resurfacing.